Efektivitas Kompos Azolla pinatta dan Arang Sekam pada Pertumbuhan Bibit Kelapa Sawit di Pre Nursery pada Tanah Latosol - Ginting, Sauza Devano; Rahayu, Enny; Andayani, Neny (AGROISTA : Jurnal Agroteknologi, 2025)
Oil palm is a favorite crop in Indonesia, because it provides good prospects in the future. Ouality oil palm seedlings are needed for oil palm development. This study aims to see the effect of various doses of Azolla pinanta fertilizer, as well as the best mixing of latosol soil and husk charcoal planting media for the growth of oil palm seedlings in the pre-nursery. The research was conducted at KP-2 Kalikuning, Maguwoharjo, Sleman Regency, Depok District, Yogyakarta Special Region Province which is located at altitude of 118 meters above sea level the research was conducted from Mei to June 024. The experimental design used was a factorial complete ramdomized design, as the first factor was the doses of azolla fertilizer consisting of 3 levels, namely D0= 0 grams/plants, D1= 10 gram/plant, and D2= 25 gram/plant. The second factor is the composition of latosol planting media: Husk charcoal which consists if 4 levels, namely V0= 100 Latosol, V1= 50%;50%, V2= 75%:25% and V3= 100% husk charcoal. 3x4x4=48 plants were needed. Observation data were analyzed by Analusis of Variance (ANOVA) at 5% real level. If there s a significant effect, it is continued with the DMRT (Duncan’t Mutliple Range Test) test at a real level of 5%. The result showed that there was no significant interaction between the dose if Azolla fertilizer and the composition of latosol planting media and husk charcoal on the growth of oil palm seedlings is PN. For planting medi Of oil plam seedling in the Pre Nursery, soil alone without husk charcoal and without Azolla fertilizer, the growth was the same as those added with husk charcoal and Azolla fertilizer